Some Japanese Shakespeare Productions in 2014-15 - Kawai, Shoichiro (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
This essay focuses on some Shakespeare productions in Japan during 2014 and 2015. One is a Bunraku version of Falstaff, for which the writer himself wrote the script. It is an amalgamation of scenes from The Merry Wives of Windsor and those from Henry IV. It was highly reputed and its stage design was awarded a 2014 Yomiuri Theatre Award. Another is a production of Much Ado about Nothing produced by the writer himself in a theatre-in-the-round in his new translation. Another is a production of Macbeth arranged and directed by Mansai Nomura the Kyogen performer. All the characters besides Macbeth and Lady Macbeth were performed by the three witches, suggesting that the whole illusion was produced by the witches. It was highly acclaimed worldwide. Another is a production of Hamlet directed by Yukio Ninagawa, with Tatsuya Fujiwara in the title role. It was brought to the Barbican theatre. There were also many other Shakespeare productions to commemorate the 450th anniversary of Shakespeare’s birth.